Influence of Sex, Race/Ethnicity, and Socioeconomic Factors on Meniscal Treatment With Pediatric and Adolescent ACL Reconstruction. Issue 11 (September 2022) - Mercurio, Angela M.; Coene, Ryan P.; Cook, Danielle L.; Feldman, Lanna; Milewski, Matthew D.
Background: The rate of anterior cruciate ligament (ACL) reconstruction is increasing over time in pediatric/adolescent populations, but there is less evidence to support how concomitant meniscal procedures are changing over time. There are also less data to suggest which characteristics are associated with meniscectomy versus meniscal repair treatment. Hypothesis: Age, sex, race/ethnicity, income, and insurance type may independently affect the rate of concomitant meniscal procedures and treatment modalities in pediatric patients with ACL reconstruction. Study Design: Descriptive epidemiology study. Methods: The Pediatric Health Information System database was queried for all patients aged ≤18 years who underwent ACL reconstruction with or without concomitant meniscal procedures from 2015 to 2019. Basic demographic data including age, sex, self-identified race/ethnicity, rural-urban commuting area code, predicted median income, and insurance status were collected. Linear regression was used to model trends and multiple logistic regression modeling was used to test for associations. Results: A total of 14, 398 patients aged ≤18 years underwent ACL reconstruction during the study period, with 8337 patients (58%) having concomitant meniscal procedures with a 1.24-fold increase over 5 years. Of the concomitant meniscal treatment cohort, 41% had a meniscectomy and 59% had meniscal repair. There was a 0.82-fold change in meniscectomy and a 1.67-fold increase in meniscal repair during the study period. Male patients, older patients, Black race, living in an urban area, and those with nonprivate insurance had increased odds of undergoing a concomitant meniscal procedure (all P < .05). Patients of non-White race and those with nonprivate insurance had increased odds of having a meniscectomy versus meniscal repair (all P < .05). There were no associations detected between income bracket and the outcomes in this study. Conclusion: This study shows that in pediatric and adolescent patients undergoing ACL reconstruction, there was a rise in concomitant meniscal procedures from 2015 to 2019. In addition, patients of non-White race and those with nonprivate insurance have increased odds of undergoing meniscectomy versus meniscal repair.